Analysis on the Implementation of Green Open Space Management Policies in Parepare City - Kasenda, Haikal; Hidayat, Ikhsan (Economos : Jurnal Ekonomi dan Bisnis, 2024)
In carrying out development, the city government should be more objective in assessing the potential impacts of planned projects. This is crucial as such developments can influence the city's growth and often result in inconsistencies in spatial planning, including green open spaces. In practice, only internal or external factors tend to influence these plans, leading to inefficiencies in managing green open spaces. For instance, internal factors may include transforming a previously non-economical green open space into an economic area without considering its benefits and function as a green space. These issues represent just a small fraction of the challenges in maintaining such spaces. According to the regulations issued by the city government in the form of regional regulations, oversight and legal enforcement are also stipulated for all parties involved in the implementation of green open space management policies in Parepare City. In this regard, the city government must adopt a more objective approach and avoid selectivity in addressing violations of these policies. Based on this rationale, the researcher is intrigued to conduct a study on this topic to analyze the existence and management of green open spaces in greater depth. The study is titled: "Analysis on the Implementation of Green Open Space (GOS) Management Policies in Parepare City."